Non - genetic factors affecting milk composition traits and association of milk quality parameters with udder and teat type traits of Sahiwal and Karan Fries cows - Sharma, Nisha; Revanasiddu D; Sushil Kumar; Beena Sinha (Indian Journal of Dairy Science, 2022)
The study was carried out to determine the effect of season of calving, stage of lactation and parity on 207 cattle compromising of Sahiwal (107) and Karan Fries cattle (100) of different parities and lactation stages.In Karan Fries cows, Season had significant effect on all milk composition traits viz., average test day milk yield (ATDMY), average test day fat yield (ATDFY), average test day solid not fat yield (ATDSNFY), average test day protein percentage (ATDP%) and average test day lactose yield (ATDLY). In Sahiwal cows, parity had non-significant effect on all milk composition traits whereas, in Karan Fries cows, parity had significant effect on milk composition traits viz., ATDMY, ATDFY, ATDSNFY, ATDP%, ATDLY and average test day protein yield (ATDPY). In Sahiwal cows, Season had non-significant effect on all milk composition traits whereas, in Karan Fries cows (KF) had significant effect on milk composition traits viz., ATDMY, ATDFY, ATDSNFY, ATDP% and ATDLY in Karan Fries cows. In Sahiwal cows, parity had non-significant effect on all milk composition traits whereas in Karan Fries cows, parity had significant effect on milk composition traits viz., ATDMY, ATDFY, ATDSNFY, ATDP%, ATDLY and ATDPY. The phenotypic correlation between udder and teat type traits and composition were low in magnitude. It can be concluded that changing patterns of milk composition with different seasons and parities provide scientific evidence to improve the nutrition management.